Relationship between Knowledge Level and Compliance with Dietary in Elderly Patients with Diabetes Mellitus in Karang Rejo Village, Langkat Regency - Tinah Tinah; Cecep Triwibowo (Universitas Islam Negeri Sumatera Utara, Medan, 2024)
Elderly refers to a more advanced phase of a physiological process marked by a decline in the body's capacity to adjust to external pressures. One contributing factor to the rise in Diabetes Mellitus is a deficiency of understanding, which can subsequently influence the adoption of harmful behaviors. Health providers propose dietary behavior as a means to normalize blood sugar levels in elderly individuals with Diabetes Mellitus. The objective of this The aim of this research is to examine the relationship between levels of knowledge and adherence to dietary recommendations among elderly adults diagnosed with diabetes mellitus who live in Karang Rejo Village, Langkat Regency. In this study, a quantitative approach is employed, utilizing a cross-sectional research design. The present investigation was carried out at Karang Rejo Village, located in the Langkat Regency, spanning from February to October 2023. The research sample consisted of 780 older individuals diagnosed with Diabetes Mellitus, residing in Karang Rejo Village, Langkat Regency. The study utilizes a basic random sampling technique to ensure that each participant has an equal probability of being chosen for the sample, without considering their individual features. Consequently, the sample size for this study consisted of 42 old individuals. The primary instrument employed for data collection in this study was a questionnaire. The present study employed bivariate analysis chi-square test for data analysis, and utilized software help in the form of SPSS version 20 for data processing. The findings indicated a statistically significant correlation (p-value = 0.001) between the extent of knowledge and adherence to dietary recommendations among older individuals diagnosed with diabetes mellitus residing in Karang Rejo Village, Langkat Regency. There is an aspiration for the senior population to enhance their knowledge and engage with information sourced from health centers and various social media platforms. Keywords: Compliance, Dietary, Elderly, Knowledge